PROBLEMATIKA MUAMALAH DI DAERAH PERBATASAN INDONESIA-MALAYSIA: Tinjauan Fiqh Terhadap Problematika Muamalah di Daerah Perbatasan Jagoi Babang Kalimantan Barat - Siregar, Hamka (The Pontianak State Institute of Islamic Studies, 2015)
The border area that becomes a regional entrance bridging two countries, Indonesia-Malaysia, is often misused by irresponsible people. Moreover, this issue was begun from the research performed in Jagoi Babang, one of the border areas in West Kalimantan. Through the research, many complicated problems found around the border area have not solved properly. Therefore, this research is written to gain some information, such as the muamalah problems, the causes of the muamalah problems, and how the moslems in the border area deal with the problems legally.